The used of microwave derived activated carbon for removal of heavy metal in aqueous solution - Herman, Anak Senghie (Universiti Malaysia Sarawak (UNIMAS), 2010)
Palm oil processing wa<;te which is palm oil kernel shell (POKS), which is both a waste and pol)utant, was converted to activated carhon through 7 minutes microwave pyrolysis at temperature 270D C and chemical activation using sodium hydroxide and hydrochloric acid, The adsorption study on Cr(IV), Ni(!!) and Cu(lI) for aqueous solution was conducted to evaluate the adsorption capacity of the activated carbon prepared. The adsorption capacity was determined as a function of adsorbate initial concentration and adsorbent dosage. Adsorption isotherms of the study were dctcnmned with Langmuir and Freundlich isotherm model. from the calculation based on Langmuir iwthenn, Ni{H) show the highest adsorption capacity of 40.98 mg'g, followed by Cr(IV) and Cu(lI) wi,h adsorption capaci,y of 40,60 mglg and 13,69 mg;g, Cr(IV) and Cu(lI) show better fitting to Freundlich isothenn model with high correlation regression indicating the applicability of heterogeneous adsorption. MOl} show bencr fitting with Langmuir isothenn that indtcate monolayer coveragc, Adsorption of Cr(lV), Ni(lI) and Cu(lI) by POKS activated carbon is dependent on adsorbent dosage and adsorption of Ni(l1) was controlled by initial metal concentration. The use ofPOKS as activated carbon is: not only effective for adsorption ofCr(lV), Ni(lI) and Cu(lI) in aqueous solution but also helps to overcome the over abundance ofPOKS waste problem.